Diverging Understandings of Forest Management in Matsutake Science - Tsing, Anna; Satsuka, Shiho (Economic botany, 2008)
As high-value gourmet mushrooms, the matsutake complex of the genus Tricholoma has been the subject of extensive research. This article reviews two trajectories of matsutake research, showing how distinctive regional nodes may develop within a cosmopolitan modern science. The global center of matsutake research is in Japan, where problems of artificial cultivation and the "orchard-style" enhancement of production under forest conditions stimulate basic research. U.S. Pacific Northwest research forms a contrasting regional node, with a focus on sustainable yields in the context of timber production. Regional differences in research design and results point to the importance of distinctive scientific legacies, in this case formed in relation to divergent histories of forest management. Attention to regional distinctions in the framing of scientific problems is particularly important as scientific frameworks are exported to new places; for example, both Japanese and American forms of matsutake science have been extended to China. /// マツタケ科学にみる書林聾理の多樺化について高価なグルメきのこであるマツタケと その近晶君重群のTrich olαna属は広範囲に渡る科学的研究の対象となってきた。本論では 二つの地域特徴的なマツタケ研究の軌跡を概観し、文化的差異を超えて世界的に通用す る近代科学においても地域固有の関心に応じて特徴のある知識が結節し発展することを 示す。マツタケ研究の世界的な中心地である日本では人工増殖やマツタケを殖やすため の「果樹園的』な山林作りへの関心が基礎研究の方向性に刺激を与えてきた。一方日本 とは対照的に、米国北西岸州では木材の持続的産出に主眼をおいた山林管理の流れの中 で研究が進んできた。こうした研究計画や結果的に得られる知識の違いは、地域ごとに 特徴のある科学的遺産ー本件の場合は森林管理の歴史が多様に枝分かれしていることー に注目することが重要であることを知らせてくれる。近年日本や米国で発展したマツタ ケ研究の方法や成巣が中国での研究にも影響を与えているが、特に新しい研究の場を広 げる場合には科学的な関心、問題がどのような枠組で組み立てられるか地域によって多 様であることを考慮することが重要である。